1996
DOI: 10.1021/es9504449
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Risk Assessment of Tributyltin Accumulation in the Food Web of a Shallow Freshwater Lake

Abstract: Tributyltin (TBT) measurements in a food web in the freshwater Lake Westeinder are used to calibrate an integrated fate and bioaccumulation model with special attention given to exposure pathways. The Dutch ban on antifouling paints containing TBT is simulated with a load reduction scenario. By integrating Monte-Carlo sampling with a calibration procedure, probability distributions of TBT concentrations in the food web are matched to the measured variation in TBT concentrations. Subsequently, these distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Further specific food chain models e.g. that for the herring gull (Norstrom et al, 1991), the aquatic food chain of Gobas (1993), the benthic and pelagic food chain of Morrison et al (1997), or for Contaminants in Aquatic and Terrestrial ecoSystems (CATS) (Traas and Aldenberg, 1994;Traas et al, 1996), may be used to improve the methodology to include secondary poisoning. However, the more complex the food chain is, the less ecotoxicological and bioaccumulation data are available to fully identify the risk of secondary poisoning (Jongbloed et al, 1994).…”
Section: The Methods Of Secondary Poisoningmentioning
confidence: 99%
“…Further specific food chain models e.g. that for the herring gull (Norstrom et al, 1991), the aquatic food chain of Gobas (1993), the benthic and pelagic food chain of Morrison et al (1997), or for Contaminants in Aquatic and Terrestrial ecoSystems (CATS) (Traas and Aldenberg, 1994;Traas et al, 1996), may be used to improve the methodology to include secondary poisoning. However, the more complex the food chain is, the less ecotoxicological and bioaccumulation data are available to fully identify the risk of secondary poisoning (Jongbloed et al, 1994).…”
Section: The Methods Of Secondary Poisoningmentioning
confidence: 99%
“…It has been reported that TPT is transferred through the food web Traas et al 1996) and low concentrations could mediate effects through bioaccumulation, resulting in a more sensitive response than in the laboratory.…”
Section: Comparing Laboratory and Field Responsesmentioning
confidence: 99%
“…Studies of TBT have typically been conducted in marine systems, with few from fresh waters (see Kannan, Senthilkumar & Sinha, ; Tessier et al ., ). There has also been a tendency to simply detail its occurrence or estimate trophic transfer between aquatic consumers only (Stab et al ., ; Traas et al ., ). Since organotins have been detected in chironomid imagos from brackish waters of the Baltic (Lilley et al ., ), we hypothesised that chironomids might be an important vector of organotins across ecosystem boundaries from freshwater to terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 97%